Fibrous hamartoma of infancy associated with bony remodeling and muscle atrophy. Issue 5 (27th June 2019) - Kozlowski, Anna; Murati, Michael; Ogilvie, Christian; Hess, Donavon; Miller, Daniel; Hook, Kristen
Abstract: Fibrous hamartoma of infancy (FHI) is a benign, poorly demarcated, unencapsulated hamartoma contiguous with surrounding fat. This case highlights pronounced bony remodeling and muscle atrophy associated with FHI in a 6‐week‐old girl. Emphasis is placed on pathologic diagnosis and mechanisms, treatment considerations, and the multidisciplinary approach utilized in the management of the disorder.